Principal Managerial Competencies for Sustaining School Accreditation: The Roles of School Planning and Program Monitoring in Quality Assurance - Lulu Fauziah; Heru Juabdin Sada; Ilhami (Journal of Educational Management Research, 2026)
This study aims to analyze the principal’s managerial competence in school planning and in implementing program monitoring and evaluation to support the sustainability of school accreditation. A qualitative descriptive approach was employed. Data were collected through interviews, observations, and document analysis, and were analyzed using the Miles, Huberman, and Saldaña interactive model, including data reduction, data display, and conclusion drawing. The findings indicate that the principal demonstrates strong managerial competence in preparing school strategic and operational plans based on educational report data, school self-evaluation, and previous program evaluation results. In addition, program monitoring and evaluation are conducted systematically through coordination meetings, academic supervision, program reporting, and follow-up actions based on evaluation findings. These managerial practices contribute to continuous quality improvement by strengthening planning, ensuring effective program implementation, and fostering evidence-based decision-making. The study implies that principals’ managerial competence plays a vital role in sustaining school quality assurance and maintaining accreditation standards through systematic planning, continuous monitoring, and ongoing evaluation.